HELP ME NOW PLEASE IM BEGGING YOU PLEASE IM CRYING IM GOING INSANE I NEED HELP WITH THIS QUESTION IM TIRED OF ASKING THE SAME QUESTION OVER AND OVER AGAIN PLEASE HELP IF YOU ARE GOOD AT MATH

HELP ME NOW PLEASE IM BEGGING YOU PLEASE IM CRYING IM GOING INSANE I NEED HELP WITH THIS QUESTION IM TIRED OF ASKING THE SAME QUESTION OVER AND OVER AGAIN PLEAS class=

Respuesta :

Answer:

-4

Step-by-step explanation:

Average rate of change: y / x = (f(x₁) - f(x₂)) / (x₁ - x₂)

Note: it does not matter which goes first- x₁ or x₂. Just keep them in the same order for both parts (just like when you find slope)

For example, if we were conducting a lab experiment and there was 40 rats in week 2 and 80 rats in week 4, then to find the average rate of change:

(40 - 80) / (2 - 4) = -40 / -2 = 20 rats per week

Now, let's apply this to the equation we have.

h(x) = -x² + 3x + 1 when x=2 and x= 5

When x = 2,

-x² + 3x + 1 = - 2² + 3*2 + 1 = -4 + 6 + 1 = 3

When x = 5,

-x² + 3x + 1 = -5² + 3*5 + 1 = -25 + 15 + 1 = -9

Now, plug these into the equation (f(x₁) - f(x₂)) / (x₁ - x₂)

Let's set x₁ as 2 and x₂ as 5. So,

(h(2) - h(5)) / (2 - 5)

Then, substitute h(2) and h(5) with the numbers we already know.

(3 - (-9)) / (2 - 5)

12 / (-3)  = -4

Thus, the answer is -4

I hope this helps! Feel free to ask any questions!